TOURISM AS A GUARANTEE OF FRIENDSHIP AND COOPERATION - Muhsina Juraboyeva (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This paper examines the role of tourism as a catalyst for international friendship and cooperation in the twenty-first century, with particular reference to the experiences of developing countries and culturally rich regions such as Central Asia. The study explores how tourism fosters intercultural understanding, diplomacy, and socio-economic interdependence among nations. It analyses tourism’s contribution to peace-building, regional collaboration, and global solidarity by focusing on both state-level initiatives and people-to-people relations. The discussion integrates theoretical frameworks of sustainable development, soft power, and cultural diplomacy, arguing that tourism—when managed responsibly—transcends economic value and becomes an enduring instrument of international harmony.